The effect of a traditional Chinese quadri-combination therapy and its component quercetin on recurrent spontaneous abortion: A clinical trial, network pharmacology and experiments-based study - Zhou, Jing; Li, Lisha; Pan, Xinyao; Wang, Jing; Qi, Qing; Sun, Hongmei; Li, Chuyu; Wang, Ling (Frontiers in Pharmacology, 2022)
Objective: To explore the effect and mechanisms of a traditional Chinese quadri-combination therapy (Bushen, Yiqi, Lixue and Yangtai, BYLY) in treating recurrent spontaneous abortion (RSA). Methods: A clinical trial was conducted to study the effect of BYLY on RSA. Pharmacological network analysis and UPLC-Q/TOF-mass spectrometry (MS) were applied to speculate the key active component in BYLY and potential targets. Cellular experiments based on former results were performed to validate the mechanisms of BYLY on the treatment of RSA. Results: Four hundred and eighty participants enrolled in the clinical trial. The results showed that comparing with using BYLY or duphaston alone, the combination of duphaston and BYLY could decrease the early abortion rate in RSA (P < 0.001). Network pharmacological analysis indicated that BYLY contained 132 active components and 146 core targets, and quercetin might be the key component taken effect. In vitro experiments found that pretreatment of quercetin at proper concentration (2 μM) prevented hypoxia-induced viability and proliferation reduction, apoptosis and mitochondrial dysfunction. Also, quercetin could modulate the mitochondrial fission/fusion balance in trophoblasts, specifically decrease the expression of Drp1 by regulating miR-34a-5p. Conclusion: BYLY could improve the pregnancy outcomes of RSA, which relied on multi-components and multi-targets. The protective effect of quercetin on trophoblasts by decreasing Drp1 expression via regulating miR-34a-5p might be one of the possible mechanisms.